Review on Building Energy Management Systems by Retrofitting Existing Buildings with Green Technology - Asmawi, Rosli; Sari, Jeremy Jimbun Anak (Research Progress in Mechanical and Manufacturing Engineering, 2024)
With global energy consumption on the rise, it is imperative to develop energy-saving measures. Since old buildings consume a significant amount of energy, it is important to assess them as a potential upgrade opportunity. Retrofitting in the context of buildings is the addition of new hardware or software components to a facility to improve its performance. Retrofitting an old building is one strategy to minimize reliance on the construction of new buildings. There are several old buildings that can be retrofitted with green technologies. Hence, the purpose of this study is to give information on the review and investigation of building energy management systems by retrofitting existing buildings with green technology. Site visits and walk-through inspections are conducted after selecting the C16 FKMP building as the study’s objective. The building’s energy consumption has been calculated, and data has been gathered. The data was then used to estimate and propose energy conservation measures such as lighting system retrofitting and solar photovoltaic systems. Retrofit should be promoted throughout the building and conservation industries due to its numerous advantages. It is one of the most eco-friendly and cost-effective strategies for optimizing energy performance and extending the lifespan of the existing building